The in vitro quality of X‐irradiated platelet components in PAS‐E is equivalent to gamma‐irradiated components. Issue 11 (5th September 2021) - Johnson, Lacey; Vekariya, Shuchna; Wood, Ben; Costa, Marylia; Waters, Lauren; Green, Sarah; Marks, Denese C.
Abstract: Background: Blood components are irradiated to inactivate lymphocytes in an effort to prevent transfusion‐associated graft versus host disease. Although gamma irradiators are commonly used, they are subjected to rigorous health, safety, and compliance regulations, compared with X‐irradiators which have the advantage of only emitting radiation while the machine is switched on. While the effects of gamma irradiation on platelet components are well known, there is little or no data comparing the effects of X‐ and gamma‐irradiation on the quality of these components. Therefore, this study examined the in vitro quality of platelet components (pooled and apheresis) following X‐ or gamma‐irradiation. Study design and methods: Whole‐blood‐derived (pooled) and apheresis platelet components in platelet additive solution ( n = 20 pairs for each type) were irradiated (X vs. gamma). In vitro platelet quality was tested prior to irradiation (day 1) and subsequently on days 2, 5, and 7. Non‐irradiated components were tested on day 5 in parallel as reference controls. Metabolic parameters, surface expression of glycoproteins and activation markers (CD62P and annexin‐V binding), and agonist‐induced aggregation were measured. Results: All components met Council of Europe specifications. There were no statistical differences in any in vitro quality measurements between X‐ and gamma‐irradiated pooled or apheresis platelet components. Conclusion: X‐ and gamma‐irradiation have similar effects on the in vitro quality of stored blood components, indicating that either technology represents a suitable option for irradiation of platelet components.